Activation of PsMYB10.2 Transcription Causes Anthocyanin Accumulation in Flesh of the Red-Fleshed Mutant of ‘Sanyueli’ (Prunus salicina Lindl.) - Fang, Zhi-Zhen; Lin-Wang, Kui; Zhou, Dan-Rong; Lin, Yan-Juan; Jiang, Cui-Cui; Pan, Shao-Lin; Espley, Richard V.; Andre, Christelle M.; Ye, Xin-Fu (Frontiers in Plant Science, 2021)
Plum is one of the most important stone fruits in the world and anthocyanin-rich plums are increasingly popular due to their health-promoting potential. In this study, we investigated the mechanisms of anthocyanin accumulation in the flesh of the red-fleshed mutant of the yellow-fleshed plum ‘Sanyueli’. RNA-Seq and qRT-PCR showed that anthocyanin biosynthetic genes and the transcription factor PsMYB10.2 were upregulated in the flesh of the mutant. Functional testing in tobacco leaves indicated that PsMYB10.2 was an anthocyanin pathway activator and can activate the promoter of the anthocyanin biosynthetic genes PsUFGT and PsGST. The role of PsMYB10.2 in anthocyanin accumulation in the flesh of plum was further confirmed by virus-induced gene silencing. These results provide information for further elucidating the underlying mechanisms of anthocyanin accumulation in the flesh of plum and for the breeding of new red-fleshed plum cultivars.